Ontogeny of the Projections From the Dorsomedial Division of the Anterior Bed Nucleus of the Stria Terminalis to Hypothalamic Nuclei - Lanzillo, Marc; Gervais, Manon; Croizier, Sophie (Frontiers in Neuroscience, 2021)
The bed nucleus of the stria terminalis (BNST) is a telencephalic structure well-connected to hypothalamic regions known to control goal-oriented behaviors such as feeding. In particular, we showed that the dorsomedial division of the anterior BNST innervate neurons of the paraventricular (PVH), dorsomedial (DMH), and arcuate (ARH) hypothalamic nuclei as well as the lateral hypothalamic area (LHA). While the anatomy of these projections has been characterized in mice, their ontogeny has not been studied. In this study, we used the DiI-based tract tracing approach to study the development of BNST projections innervating several hypothalamic areas including the PVH, DMH, ARH, and LHA. These results indicate that projections from the dorsomedial division of the anterior BNST to hypothalamic nuclei are immature at birth and substantially reach the PVH, DMH, and the LHA at P10. In the ARH, only sparse fibers are observed at P10, but their density increased markedly between P12 and P14. Collectively, these findings provide new insight into the ontogeny of hypothalamic circuits, and highlight the importance of considering the developmental context as a direct modulator in their proper formation.